2016
DOI: 10.1142/s0217751x16501256
|View full text |Cite
|
Sign up to set email alerts
|

Exact lattice supersymmetry at the quantum level for N = 2 Wess–Zumino models in 1- and 2-dimensions

Abstract: Supersymmetric lattice Ward-Takahashi identities are investigated perturbatively up to two-loop corrections for super doubler approach of N = 2 lattice Wess-Zumino models in 1-and 2-dimensions. In this approach notorious chiral fermion doublers are treated as physical particles and momentum conservation is modified in such a way that lattice Leibniz rule is satisfied. The two major difficulties to keep exact lattice supersymmetry are overcome. This formulation defines, however, nonlocal field theory. Neverthel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 93 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…In fact we found a formulation of the N = 2 Wess-Zumino models in one and two dimensions which have exact SUSY on the lattice [16,17]. It has been also confirmed that SUSY on the lattice is preserved even at the quantum level [19]. It has, however, been recognized that associativity for the -product is broken:…”
Section: Difficulties Of Lattice Susy and The Possible Solutionssupporting
confidence: 57%
See 1 more Smart Citation
“…In fact we found a formulation of the N = 2 Wess-Zumino models in one and two dimensions which have exact SUSY on the lattice [16,17]. It has been also confirmed that SUSY on the lattice is preserved even at the quantum level [19]. It has, however, been recognized that associativity for the -product is broken:…”
Section: Difficulties Of Lattice Susy and The Possible Solutionssupporting
confidence: 57%
“…In order to recover the associativity for the -product we notice that if momentap i does not have upper limit in (18); then 2 a is replaced by ∞ in (19) and associativity is recovered. For this reason we tried to find an alternative lattice translation generator ∆(p) with the following properties:…”
Section: Difficulties Of Lattice Susy and The Possible Solutionsmentioning
confidence: 99%
“…Non-associativity does not sacrifice exact lattice SUSY for non-gauge cases. In fact exact SUSY has been confirmed even at the quantum level [15]. We have proposed a new lattice SUSY formulation by the use of ∆ G as a differential operator.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Nevertheless the resulting lattice theories had exact supersymmetry, even at the quantum level [51].…”
Section: Jhep12(2017)089mentioning
confidence: 99%